'Let me edutain you...' Moving Image Education and young people not in education, employment or training - George Head (University of Aberdeen, School of Education, 2009)
Whilst Media Studies has been taught in Scottish Schools for several decades and film has been used as an educational medium for most of the Keywords: media literacy; moving image education; non-formal education; pedagogy; Century, Moving Image Education is a recent Scottish Screen development aimed at helping young people engage with, appreciate and create their own moving images. As a consequence of the experiences of pupils and teachers using moving images in mainstream schools Scottish Screen and Scottish Enterprise Glasgow (now Skills Development Scotland) felt that it was an appropriate programme for young people who at that time were considered to be not in employment, education or training but who were, in fact, attending the Get Ready for Work programme offered by Scottish Enterprise through training providers. This paper is based on an evaluation of that project commissioned by Scottish Screen and undertaken by the author. The paper begins by making a case for the place of Moving Image Education in young people's lives. It then recounts the experiences of the young people and trainers involved in this study, and offers an explanation of why the programme worked in the way that it did